2016
DOI: 10.1007/s13353-016-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of miRNA profiling during airway epithelial repair in undifferentiated and differentiated cells in vitro

Abstract: Respiratory epithelium is a highly integrated structure that efficiently protects lungs from extrinsic irritants thanks to rapid repair of the wound. The repair is a complex process that requires coordinated expression of networks of genes. Plausible regulators of this process are microRNAs. We investigated if global miRNA silencing influences the epithelial repair and if changes in miRNA expression profile during repair are similar between two bronchial epithelial cell cultures: differentiated and undifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…That corresponds to the results of our previous research [ 15 ], reporting changes in miRNA expression in undifferentiated cell line (16HBE14o-). Our recent findings [ 21 ] have also confirmed the importance of miRNA during this process: silencing of DICER and DROSHA , the enzymes crucial for RNA interference, resulted in significantly delayed wound repair. Profiling analysis of both cell types (undifferentiated and pseudostratified epithelium) showed some similarities between the expressions of several miRNA genes, suggesting their importance in the fundamental repair processes.…”
Section: Discussionsupporting
confidence: 67%
“…That corresponds to the results of our previous research [ 15 ], reporting changes in miRNA expression in undifferentiated cell line (16HBE14o-). Our recent findings [ 21 ] have also confirmed the importance of miRNA during this process: silencing of DICER and DROSHA , the enzymes crucial for RNA interference, resulted in significantly delayed wound repair. Profiling analysis of both cell types (undifferentiated and pseudostratified epithelium) showed some similarities between the expressions of several miRNA genes, suggesting their importance in the fundamental repair processes.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, the results were not confirmed in differentiated epithelial cells, using the air‐liquid interface (ALI) model. However, others have shown that NHBE in ALI close by only 20% even at 48 hours, which was suggested to be due to technical issues with using ALI for wound repair assays.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been intensively studied and today we understand that these molecules regulate several cellular and developmental pathways. MicroRNAs have shown differing expression patterns during tissue repair in bones 15 , 16 , lungs 17 skin 18 , 19 and oral mucosa 20 . These molecules mostly contribute to tissue repair by coordinating cell proliferation and inflammation among other functions 18 , 19 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%